Integration of Transverse Isotropy in the Instantaneous Behaviour of Geomaterials with Application to Numerical Modelling of Underground Structures - Djouadi, Inès; Giot, Richard; Raude, Simon; Cuvilliez, Sam; Laigle, François; Fernandes, Roméo (Geotechnical and geological engineering, 2020)
The paper deals with the integration of structural anisotropy in a pre-existing constitutive law for rocks, dedicated to the numerical modelling of underground structures. On the basis of bibliographic study, two approaches were selected and applied to a simple constitutive law to begin with, namely the Drucker–Prager model. The two appraoches considered are the fabric tensor approach and the weakness plane approach. Both approaches are described, the equations are provided and the resulting anisotropic models are implemented in the open source finite element software (Code_Aster in EDF R&D code général pour l’étude du comportement mécanique des structures diffusé sous licence GNU GPL, 2017). The models are then applied to the simplified numerical modelling of an underground facility and the main results are provided. The main advantages and drawbacks of both approaches are highlighted. The main findings of this work is that the fabric tensor approach is the most fitted for the material considered for the future prospects. The future prospects are the integration of anisotropy in a much more complex isotropic model being developed by EDF research team for application to geomaterials.